The Effectiveness of Acceptance and Commitment-Based Training on Reducing Occupational Stress and its Components among Administrative Employees - Parsaei , Maryam; Naseri, Ali (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to investigate the effectiveness of acceptance and commitment-based training on reducing occupational stress and its components among administrative employees of Shiraz University of Medical Sciences. The research employed an applied, quantitative, semi-experimental design with a pre-test–post-test control group and a two-month follow-up. The statistical population comprised all administrative employees of Shiraz University of Medical Sciences in 2024, from which 66 participants were selected through convenience sampling and randomly assigned to experimental (n = 33) and control (n = 33) groups. The experimental group received eight sessions of acceptance and commitment-based training based on Steven Hayes’ protocol, while the control group received no psychological intervention during the study period. Data were collected using the Occupational Stress Questionnaire developed by Turnic and Spielberger (1991), whose validity and reliability had been previously confirmed (Cronbach’s alpha = 0.87). Data analysis was conducted using univariate and multivariate analysis of covariance (ANCOVA, MANCOVA) in SPSS 28, after verifying parametric assumptions. The results revealed that, after controlling for pre-test scores, the experimental group showed significantly lower post-test mean scores compared to the control group in total occupational stress (F = 99.30, p < 0.001, η² = 0.623) and in several subcomponents, including task performance (F = 38.55, p < 0.001, η² = 0.421), participation and decision-making (F = 14.99, p < 0.001, η² = 0.220), responsibility (F = 74.22, p < 0.001, η² = 0.583), support (F = 18.11, p < 0.001, η² = 0.255), and relationships (F = 11.89, p = 0.001, η² = 0.183). No significant differences were observed for work environment, competition, or promotion/reward. These effects persisted at follow-up, indicating sustained intervention benefits. Acceptance and commitment-based training effectively reduced occupational stress and improved key stress-related components in administrative healthcare employees, with effects maintained over two months.